From Zamboanga to Subic and Clark: Conflict and Cooperation in Ancestral Domains and Economic Zones - Alejo, Albert E. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
Can an economic zone coexist peacefully and productively with an indigenous community? How can the friction between land use and land ownership be negotiated? And is legal battle the only nonviolent platform for settling land disputes? These questions were at the heart of the decade-long tug-of-war between the Zamboanga City Special Economic Zone Authority (ZAMBOECOZONE) and the Subanon tribe of Zamboanga City. As a result of dialogue, fifteen representatives from the National Commission on Indigenous Peoples Region IX, the ZAMBOECOZONE, the Labuan-Patalon-Limpapa Subanon Indigenous Cultural Organization, the Silsilah Dialogue Movement, and the Ateneo de Zamboanga University embarked on a joint study tour to Subic Bay Metropolitan Authority and to Clark Development Corporation from 8 to 10 January 2014. This research note offers both a narrative of that solidarity journey and a comparative three-way analysis of the Subic, Clark, and Zamboanga experiences. It concludes that despite the legal, cultural, and technical challenges, the overlap of their territories of conflict can still become a zone of partnership—with creative and selfcritical contribution from university academics, government agencies, and dialogue activists.
Keywords: Zamboanga City; Subanon; ancestral domain; economic zone; dialogue; Subic; Clark